Investigating the Role of Geomorphology Factors on the Establishment and Decay of the Historical Site of the Geriran in the Alshtar Plain in Lorestan Province - fariba beghipoor motlag; Aghil Madadi; iraj jabbari (جغرافیا و توسعه, 2018)
Geomorphology is one of the natural factors which has played on outstanding role in establishing settlements, such as Geriran hill, in North Aleshtar plain. in the present study , considering geomorphology and historical this site, and considering this question have been considered to the geomorphology, The geomorphology features of this site were examintion.in this study, with respect to geomorphological and historical features Geriran , using satellite images, topographic and geological maps.In order to understand the role of geomorphological elements in the establishment of historical site Geriran in north Aleshtar a series of geomorphological and sedimentological studies have been carried out, sedimentological surveys and geomorphological maps in this study can greatly contribute to archeological studies . Analysis of the results showed that adequate water and fertile sediments provided a basis for establishment of sustainable settlement, As well as the evacuation of this site in 1356 and has been due to archeology survey.however geomorphological factors have had a little effects on the site, replacement and destruction. these patterns reflected condditions considering geomorphological features in the establishment of this settlement.